2013
DOI: 10.5513/jcea01/14.4.1352
|View full text |Cite
|
Sign up to set email alerts
|

Crumb Texture of Spelt Bread

Abstract: The bread quality is considerably dependent on the texture characteristic of bread crumb. Crumb texture is an important quality indicator, as consumer prefer different bread taste. Texture analysis is primarily concerned with the evaluation of mechanical characteristics where a material is subjected to a controlled force from which a deformation curve of its response is generated. It is an objective physical examination of baked products and gives direct information on the product quality, oppositely to dough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…A comparative study with spelt varieties showed acceptable sensory scores with significant differences among the varieties (Korczyk Szabó and Lacko Bartošová ), leading to conclude that spelt might be a suitable raw material for bread making, but it remains closely related to the choice of spelt variety (Korczyk Szabó and Lacko Bartošová ). Compared to common bread, spelt genotypes had high crumb elasticity, but low crumb cell homogeneity, which are probably due to its special dough rheological attributes (Callejo and others ).…”
Section: Ancient Grains‐based Foodstuffs: Nutritional Added Value Andmentioning
confidence: 99%
“…A comparative study with spelt varieties showed acceptable sensory scores with significant differences among the varieties (Korczyk Szabó and Lacko Bartošová ), leading to conclude that spelt might be a suitable raw material for bread making, but it remains closely related to the choice of spelt variety (Korczyk Szabó and Lacko Bartošová ). Compared to common bread, spelt genotypes had high crumb elasticity, but low crumb cell homogeneity, which are probably due to its special dough rheological attributes (Callejo and others ).…”
Section: Ancient Grains‐based Foodstuffs: Nutritional Added Value Andmentioning
confidence: 99%
“…Objective texture analysis showed that sorghum bread made with tapioca starch plus HPMC was significantly firmer and had significantly lower resilience than bread made with rice starch plus xanthan gum and potato starch plus xanthan gum (Table ). Softer (less firm) bread crumb with higher resilience is often related to higher consumer satisfaction . Bread made with tapioca starch plus HPMC was less moist, less resilient and crumblier, resulting in a less desirable texture/mouthfeel than loaves made with rice starch plus xanthan gum or potato starch plus xanthan gum.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the crumb structure, several factors can be taken into account and the most common factors considered in most researches are crumb appearance, product volume [ 8 , 44 50 ], resilience of the product [ 8 ], crumb color [ 8 , 9 , 16 , 38 ], consumer appeal [ 2 , 8 , 11 , 16 , 51 – 53 ], physical texture of the product [ 7 – 9 , 46 , 54 – 57 ], taste [ 8 , 9 ], compactness and uniformity of the crumb grains [ 58 ], size, shape, uniformity, and wall thickness of crumb cells or pores [ 2 , 7 , 8 , 16 , 17 , 30 , 58 , 59 ].…”
Section: Porous Crumb Structure Developmentmentioning
confidence: 99%
“…Crumb grain has been defined in literature as the exposed cell structure of crumb when a leavened baked product is sliced [ 5 – 7 ] which can be generally seen as a two-phase soft cellular solid, consisting of a solid phase apparent in the cell wall structure and a fluid phase made up of air [ 8 , 9 ]. According to materials science approach, solid cellular materials can be categorized basically as open or closed cell foam.…”
Section: Introductionmentioning
confidence: 99%